Sociality, Seriousness, and Cynicism: A Response to Ronald Santoni on Bad Faith. Issue 1 (1st June 2020) - Webber, Jonathan
Abstract: This article is a clarification and development of my interpretation of Sartre's theory of bad faith in response to Ronald Santoni's sophisticated critique, published in this issue. It begins by clarifying Sartre's conception of a project and explaining his claim that one project is fundamental, thereby elucidating the idea that bad faith is a fundamental project. This forms the groundwork of my responses to Santoni's critique of my interpretation, which comprises four arguments: Sartre does not consider us to be ontologically and congenitally disposed to bad faith; Santoni is right that social pressure cannot explain the prevalence of bad faith, but this is a problem with Sartre's theory rather than a problem for my interpretation of it; Sartre's conception of seriousness is merely an optional strategy of bad faith; and Sartre is right to deny that bad faith is an inherently cynical project.